165 Human atherosclerosis is characterised by oxidative dna damage due to defective base excision repair. (5th June 2017) - Shah, Aarti; Gray, Kelly; Figg, Nichola; Bennett, Martin
Abstract : Rationale: Human atherosclerotic plaques show extensive oxidative DNA damage in vascular smooth muscle cells (VSMCs) and macrophages, including accumulation of 8-oxo-7, 8-dihydroguanine (8-oxoG), the most abundant DNA base lesion on oxidative exposure. 8-oxoG is repaired by base excision repair (BER) mediated by DNA glycosylases, including the specific non-redundant 8-oxoguanine DNA glycosylase-1 (OGG1). OGG1 activity is regulated by acetylation through the p300 acetyltransferase. However, the role of oxidative damage in VSMC function and the regulation of OGG1 in atherosclerosis are unknown. Methodology: We stably expressed OGG1 or the K338/K341 OGG1 acetylation mutant in rat VSMCs in vitro, and treated cells with oxidative stress. The functional effects of OGG1 in vivo were studied using global OGG1 -/- mice and novel VSMC-specific transgenic mice lines expressing OGG1 or K338/K341 OGG1. BER activity was measured via incision cleavage of an 8-oxoG-containing oligonucleotide, 8-oxoG levels by ELISA, and protein binding/interaction by immunoprecipitation and western blotting. OGG1, acetyl OGG1, p300, and 8-oxoG expression were assayed in mouse arteries and human plaques by immunohistochemistry. Results: Nuclear BER activity was defective in atherosclerotic plaque VSMCs, which correlated with a concomitant decrease in acetylation of OGG1 and OGG1 protein expression. In vitro knockout of OGG1 by CRISPR/CAS9 indicated that OGG1 is the major BER DNA glycosylase in VSMCs. Consistently, OGG1 expression increased BER activity and reduced 8-oxoG levels in vitro and in vivo, features not seen with the K338/K341 OGG1 acetylation mutant, indicating that acetylation regulates OGG1 activity in human VSMCs. OGG1 knockout cells displayed increased sensitivity to DNA breaks induced by oxidant stress and increased apoptosis compared to control cells, measured by comet assay and Annexin-V/propidium iodide FACS staining respectively. This effect was blunted by overexpression of OGG1 but not K338/K341 OGG1, suggesting a protective effect of OGG1 against DNA damage, and that the acetylation status of OGG1 is crucial for its function. Immunoprecipitation studies showed that p300 binds to OGG1, and this interaction was reduced under oxidative stress. Furthermore, levels of p300 were decreased in human plaque VSMCs and in response to oxidative stress, suggesting that ROS-induced regulation of OGG1 acetylation could be due to ROS-induced decreased in p300 expression and regulation of its interaction with OGG1. Conclusions: In conclusion, nuclear BER activity is reduced in human atherosclerotic plaque VSMCs, associated with reduced OGG1 acetylation and activity, potentially mediated by reduced p300. Mice with decreased and increased OGG1 will be used to study whether oxidative damage promotes plaque progression in atherosclerosis.